2011
DOI: 10.1002/ejoc.201101270
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective Mannich Reaction of Chiral Enolates Formed by Enantioselective Conjugate Addition of Grignard Reagents

Abstract: Cu–Taniaphos‐catalyzed enantioselective addition of Grignard reagents to cyclic enones leads to chiral magnesium enolates. These enolates add to N‐protected imines directly, or through in situ transformation to silyl enol ethers. Diastereoselectivity of the addition depends on the nitrogen protecting group of the imine. Diastereoisomers of the resulting β‐amino carbonyl compounds can be separated and are obtained in acceptable yields and in high enantiomeric purities (up to 99:1 er).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Calculated structures of TS of enolate addition to imines explain that for the sterically less congested imines (protected with Ts, Ms, Boc, and Bz) Si face attack is preferred and leads to the formation of ( R , R , S )- 61 as the major diastereomer (Scheme , TS1 vs TS2). On the other hand, with POPh 2 47b dr 1:4 was observed, and imine is attacked from the Re face, leading to ( R , R , R )- 62 as the major diastereomer (Scheme , TS3 vs TS4) …”
Section: Enolates Generated By the Catalytic Conjugate Addition Of Or...mentioning
confidence: 99%
See 1 more Smart Citation
“…Calculated structures of TS of enolate addition to imines explain that for the sterically less congested imines (protected with Ts, Ms, Boc, and Bz) Si face attack is preferred and leads to the formation of ( R , R , S )- 61 as the major diastereomer (Scheme , TS1 vs TS2). On the other hand, with POPh 2 47b dr 1:4 was observed, and imine is attacked from the Re face, leading to ( R , R , R )- 62 as the major diastereomer (Scheme , TS3 vs TS4) …”
Section: Enolates Generated By the Catalytic Conjugate Addition Of Or...mentioning
confidence: 99%
“…On the other hand, with POPh 2 47b dr 1:4 was observed, and imine is attacked from the Re face, leading to (R,R,R)-62 as the major diastereomer (Scheme 18, TS3 vs TS4). 67 Schmalz's phosphane phosphite ligand L13 brought about another improvement to the protocol mentioned above. This ligand allowed a broader scope of the tandem CA−Mannich reaction (Scheme 19a).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Sebesta and Galeštaková reported a novel copper-Taniaphos-catalyzed enantioselective conjugate addition of Grignard reagents to cyclic enones, followed by diastereoselective Mannich reaction of the in situ generated magnesium enolate to N-protected imines. 78 In this study, the authors demonstrated the interesting influence of the imine protecting group on the diastereoselectivity of enolate addition. The reaction with cyclohexenone and meth-ylmagnesium bromide in tert-butyl methyl ether followed by addition of the imine in 2-methyltetrahydrofuran (mTHF) afforded a range of enantioenriched products syn-197 and anti-197 with moderate to good stereoselectivities.…”
Section: Scheme 50 Preparation Of a β-Amino Ester By Oxidation Of Thementioning
confidence: 78%
“…The stereoselective Mannich reactions are also performed with stoichiometric amounts of chiral reagents. In these reactions, the stereochemical information could be provided by a chiral imine, in which most commonly a chiral auxiliary is a substituent of the iminic nitrogen, or by a chiral nucleophile derived from aldehydes, ketones, esters, or enol ethers . Among chiral imines, those derived from tert -butanesulfinamide have been extensively used as electrophiles over the past decade in many synthetic transformations, due mainly to the ready availability of both enantiomers of tert -butanesulfinamide at reasonable prices, the easy deprotection of the resulting amine under mild acidic conditions and the possibility of recycling the chiral auxiliary .…”
Section: Introductionmentioning
confidence: 99%